Hladkyi Ya. M., Makovkin O. M. Tribo-behaviour of instrumental steels "У8А" and "ХВГ" in the process of friction and wear. - Гладкий, Я.М.; Маковкін, О.М. (Problems of Tribology, 2014)
There has been established the regularity and wear behavior of instrumental materials «У8А» and «ХВГ» with wear-resistant coatings applied in different ways depending on friction modes changing. There has been established the physical value of triblological parameters and their change in the process of friction. It has been shown that a several times change of the contact area doesn’t influence the change of the friction factor. The change of the friction factor is caused as a rule by a chemical composition of secondary structures, which in their turn depend on a chemical composition of a basis, coating, environment and the temperature in the friction area and depends on the friction modes. There has been established the chemical composition of the secondary structures formed during friction. In general, friction is a very complex process, which can hardly be nowadays described mathematically, absolutely for any conditions, that is why the experimental research remains the main trend of defining tribo-behaviour of friction pairs. On the basis of experimental tribo-technical and microstructural research it has been established that: Under the influence of high temperatures and high specific pressures on the local areas there are formed secondary structures of a corresponding chemical composition, that significantly influence the process of friction and wear, lowering the friction factor, temperature and wear intensity. The change of the friction factor almost is not influenced by the total are of the contact. As there was used the sample with a spherical friction surface, in the process of wear the contact area was constantly growing. At the beginning of the tests the contact was in the point, and in the process of wear the area was increasing dozens of times, the fact which was not causing any changes in the friction factor behavior. The main influence on the change of the friction factor is made by secondary structures, and namely their chemical composition. The modes of friction aren’t directly influencing the friction factor, which can be seen as exemplified by “ХВГ” steel. The given steel in modes 2, 3, 4 has the same tribological characteristics and the same chemical composition of the secondary structures, that proves that the protective films are identical, which serve as a barrier for wear. The instability of friction factor is explained by the presence of oxidizing films, which periodically form and ruin due to wear. On such areas there is observed the dynamic behaviour of the friction factor change, the same thing happens with the temperature, but in a less manifested way, the fact, that to our mind, is the result of thermo-pair inertness and material thermal conductivity. Accumulation of all positive or negative processes, which are regulated by the friction modes causes the transition from one type of wear to another one (for instance from the adhesive to the fatigue one, or vice versa). The coating of an insignificant thickness 10…20 mcm (chemical chromium (ЯНГ) and the combined coating Al2O3-Ni) are essentially influencing the processes of instrumental steels wear, becoming totally different as compared with the samples without coating. Despite the insignificant thickness of the coating (tenth of mcm) and its instantaneous wear at the first minutes of testing, the particles of the latter are spread all over the friction surface and serve as a dry lubricating material.